Analisis Standar Belanja Kegiatan Penyediaan Alat Tulis Kantor Pada Pemerintah Kota Sungai Penuh - Rina Widyanti (Journal Development, 2015)
Analysis of Expense Standards (ASB) is a guideline used to analyze the reasonableness of workload or cost of each activity undertaken by the Unit (SKPD) in one fiscal year. The purpose of this research is to develop ASB especially for activity provision of stationery (ATK). The data used in this research is secondary data obtained from the DPA-SKPD Sungai Penuh City government. The primary data of interviews with leaders and some of the staff as well as the relevant officials. Data analysis method used is a simple regression. Simple regression analysis is a method of forecasting which will predict the cost standards for ATK activities. This activity is affected by the triggering factors (cost drivers) is the amount of activity. The results of this study in the form of equations where the standard shopping ASB ATK influenced by the activity of providing fixed expenditure and expenditure variables. Shopping variable for this activity is influenced by the amount of activity. To create a model for the analysis of expenditure standard ATK activity is grouped into nine (9) functions of government services consisting of the economic service./unction, the function of health care, educational services, protective services, public services, tourism services and security, public services and housing facilities, service districts, and village services. Verify the reasonableness of calculations based on the formulation of the model ASB shopping on 9 functions of government services shows that the value of expenditure contained in each DPA SKPD can be approved based on the criteria of fairness shopping. However, there are obstacles in the processing of data in the form of data on some SKPDs DPA form the basis of ASB which included incomplete and the allocation of its budget is too high thus affecting the results of the formulation ASB. It is hoped that this study provides an overview to the team of local government budgets to increase performance budgeting in the future.